2019
DOI: 10.21608/bjas.2019.187161
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Forkhead Box P3 (FOXP3) Immune-Expression in Vitiligo Patients

Abstract: The exact etiology of vitiligo remains obscure. Studies have indicated a role for cellular immunity in the pathogenesis of vitiligo. The aim of this study is to assess tissue FOXP3+ natural regulatory T-cells (Tregs) in active vs. stable nonsegmental vitiligo. Immunohistochemical staining for expression of FoxP3 in lesional, marginal, and nonlesional skin of nonsegmental vitiligo was used to evaluate the abundance of Tregs in active and stable cases of vitiligo. Reduction in the number of FOXP3-expressing Treg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, different studies from Egypt involved the relation between FOXP3 and vitiligo. A study found a marked reduction in FOXP3+ Treg cells in marginal skin lesions when compared with lesional and non-lesional skin of the same patient 54 . mRNA 164a and FOXP3 expression were studied in patients with non-segmental vitiligo, and there was increased mRNA expression while FOXP3 expression was decreased.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, different studies from Egypt involved the relation between FOXP3 and vitiligo. A study found a marked reduction in FOXP3+ Treg cells in marginal skin lesions when compared with lesional and non-lesional skin of the same patient 54 . mRNA 164a and FOXP3 expression were studied in patients with non-segmental vitiligo, and there was increased mRNA expression while FOXP3 expression was decreased.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, histopathological analysis of skin biopsies increased the numbers of cytotoxic T cells and reduced Treg numbers 29 . In addition to the number of Treg defects in vitiligo, function reduction has also been detected 30 .…”
Section: Introductionmentioning
confidence: 99%